Effectiveness of a Smoking Cessation Intervention for Methadone-Maintained Women: A Comparison of Pregnant and Parenting Women - Amber M. Holbrook; Karol A. Kaltenbach (International Journal of Pediatrics)
Women in substance abuse programs have high rates of smoking. Pregnancy represents a unique opportunity for intervention, but few data exist to guide tailoring of effective interventions. In this study, 44 pregnant and 47 nonpregnant opioid-dependent women enrolled in comprehensive substance abuse treatment received a 6-week smoking cessation intervention based on the 5A's counseling model. The number of daily cigarettes decreased by 49% for pregnant patients and 32% for nonpregnant patients at the 3-month followup. Length of time in substance abuse treatment did not correlate with smoking cessation or reduction for either group. Factors predicting reduction of cigarette smoking differed for pregnant versus nonpregnant patients. For pregnant patients, lower levels of nicotine use prior to intervention and self-reported cigarette cravings predicted successful reduction in smoking. For nonpregnant patients, lower affiliative attachment to cigarettes, reliance on cigarettes for cognitive enhancement, and greater sense of control predicted more successful outcomes.